Science Around Us: Development of a Community-based Science Curriculum for Local Preschools in the Philippines - Greg Tabios Pawilen (Unnes Science Education Journal, 2023)
Teaching science for preschool children is essential in setting the foundation for science literacy and in kindling young children’s interest in learning science. Hence the goal for designing a culturally relevant science curriculum is a gigantic challenge to all preschool teachers. This study proposed a community-based science curriculum for local preschools in northern Philippines. It supports the idea that nature should be utilized in nurturing the interest of young children in learning science. Qualitative method was used in gathering data from parents, teachers, and community leaders. Community resources that could be utilized for learning scince were identified, the legal framework for preschool education was analyzed, and the current national curriculum standards for kindergarten was analyzed to design and develop a science-based curriculum for young children. The result, which is a proposed curriculum, integrates cultural scripts, indigenous knowledge and practices, learners’ interests and needs, and community resources in the selection of curriculum contents and learning experiences. The proposed community-based science curriculum could be a model for developing a culturally relevant and responsive education for indigenous people.